Application of Nanotechnology in Thrombus Therapy. Issue 7 (16th January 2023) - Zhou, Shuyin; Zhao, Wenbo; Hu, Jinglei; Mao, Chun; Zhou, Min
Abstract: A thrombus is a blood clot that forms in the lumen of an artery or vein, restricting blood flow and causing clinical symptoms. Thrombosis is associated with many life‐threatening cardiovascular diseases. However, current clinical therapeutic technologies still have many problems in targeting, enrichment, penetration, and safety to meet the thrombosis treatment needs. Therefore, researchers devote themselves to developing nanosystems loaded with antithrombotic drugs to address this paradox in recent years. Herein, the existing thrombosis treatment technologies are first reviewed; and then, their advantages and disadvantages are outlined based on a brief discussion of thrombosis's definition and formation mechanism. Furthermore, the need and application cases for introducing nanotechnology are discussed, focusing on thrombus‐specific targeted ligand modification technology and microenvironment‐triggered responsive drug release technology. Then, nanomaterials that can be used to design antithrombotic nanotherapeutic systems are summarized. Moreover, a variety of drug delivery technologies driven by nanomotors in thrombosis therapy is also introduced. Last of all, a prospective discussion on the future development of nanotechnology for thrombosis therapy is highlighted. Abstract : Clinical therapeutic technologies still have many problems in targeting, enrichment, penetration, and safety to meet the thrombosis treatment needs. Hence, drug‐loaded nano‐delivery technologies capable of targeted delivery with good retention and permeability are the hope to improve thrombus dissolution rates and reduce bleeding risk.